Searching for Hindu nationalism in modern Indian history: analysis of some early ideological developments - Zavos, John (1999)
By tracing the ideological developments of the Hindu Sabha movement in the first decade of the 20th century in north-west India, this paper argues that development of Hindu nationalism as an ideology needs to be identified autonomous of Hindu communalism which emerged in the 1920s as a historical condition channelling ideological forces of Hindu nationalism towards particular objectives. Moreover, the Morley-Minto reforms of 1909, which aimed to restore faith in the representativeness of the colonial state and thus with over the moderates within the Congress, also instituted representative politics in terms of Hindu and Muslim identities. It was this legitimacy given to religious identities which, the paper argues, spawned Hindu nationalism as reflected in the Hindu Subhas in Punjab, who, as against the Congress extremists' call for boycott of representative politics, argued for Hindu unity so as to enforce greater representation of Hindus in legislative bodies. - Reproduced
Keywords: India - History; Nationalism - India; Nationalism